Guidelines for coconut germplasm movement amended - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
As part of research into the damaging disease in coconuts caused by the cadang cadang viroid, it was noticed that Pacific coconuts had viroid-like nucleic acid sequences present in their tissues, although this appeared to be unassociated with...